Pathogenetic Importance and Therapeutic Implications of NF-κB in Lymphoid Malignancies - Lim, Kian-Huat (2012)
Derangement of the nuclear factor κB (NF-κB) pathway initiates and/or sustains many types of human cancer. B-cell malignancies are particularly affected by oncogenic mutations, translocations, and copy number alterations affecting key components the NF-κB pathway, most likely owing to the pervasive role of this pathway in normal B cells. These genetic aberrations cause tumors to be ‘addicted’ to NF-κB, which can be exploited therapeutically. Since each subtype of lymphoid cancer utilizes different mechanisms to activate NF-κB, several different therapeutic strategies are needed to address this pathogenetic heterogeneity. Fortunately, a number of drugs that block signaling cascades leading to NF-κB are in early phase clinical trials, several of which are already showing activity in lymphoid malignancies.